Measuring Tight and Loose Cultures across NUTS-2 Regions: The Regional Index of Looseness - Vincenzo Alfano; Salvatore Ercolano (Center for Economic Studies and ifo Institute (CESifo), 2023)
This investigation quantifies the levels of cultural tightness and looseness prevalent in European societies, focusing on NUTS-2 regional divisions. Cultural dynamics occupy a pivotal role in shaping individual decision-making, particularly when addressing global risks like pandemics, environmental crises, and resource depletion. In an innovative approach, we introduce the Regional Index of Looseness (RIL) as a means to operationalize society's positioning along the spectrum of tightness-looseness. In contrast to previous cross-country studies, we harness regional data to acknowledge the intrinsic regional variations within European nations. The RIL index appraises two facets of looseness: the horizontal and vertical dimensions, providing a more nuanced understanding of societal values. The application of the RIL index to the investigation of its impact on vaccination choices and the effectiveness of NPIs offers invaluable insights for policymakers grappling with the management of global risks. This research presents a novel perspective at the regional level and scrutinizes the multi-dimensional aspects of cultural tightness and looseness.
Keywords: Z13; O57; I18; 330; tightness; looseness; culture; regional studies